2001
DOI: 10.4015/s1016237201000042
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Collagen in Medical Devices

Abstract: Collagen is the most abundant natural protein found in living systems. While there is a whole family of different collagen types, each differing in sequence, the properties that make this protein so attractive as the building blocks for medical devices, are reflected largely by the unique fibrillar structure of the molecule, as well as defined functional regions that interact with the surrounding cells and other matrix components. As a commercial medical product, collagen can be part of the natural tissue used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
0
17
0
2
Order By: Relevance
“…The swelling ratio was a simulative test for that form-stability of sponge materials under physiological conditions. In general, the swelling ratio of materials decreases as the extent of cross-linking increases [25]. The swelling ratios significantly ( p<0.05) reduced when the ratio of BF collagen increased.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The swelling ratio was a simulative test for that form-stability of sponge materials under physiological conditions. In general, the swelling ratio of materials decreases as the extent of cross-linking increases [25]. The swelling ratios significantly ( p<0.05) reduced when the ratio of BF collagen increased.…”
Section: Discussionmentioning
confidence: 95%
“…The EDC cross-linking system is frequently used in the porous collagen materials [5,9,11,14,15], which has shown better biocompatibility than glutaraldehyde (GA) [9]. In principle, the EDC cross-linking takes place by the reaction between carboxyl groups of glutamic acid and aspartic acid and generated stable amide bonds [9,11,[13][14][15]24,25]. A previous study [26] indicated that the biostability of materials could not be enhanced by external glutamic acid addition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) Collagen has been successfully employed in hydrogel form or as cell culture substrates with several collagen-based matrices for tissue regeneration in commercial use. (20) However, collagen-based constructs are inherently mechanically weak and are susceptible to shrinkage as they cannot withstand the forces exerted due to cell contraction. (21,22) To alleviate such limitations, we chose to combine collagen as a biological coating agent on covalently crosslinked alginate structure, which provides mechanical reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its development as a drug delivery device has been overshadowed by advances in synthetic polymers in the past decade owing to its low dimensional and mechanical stability and rapid swelling properties [2]. As a result, modification processes such as crosslinking [13] are usually employed to improve the physicochemical properties of collagen-based structures.…”
Section: Introductionmentioning
confidence: 99%